Circulating Cellular Communication Network Factor 1 Protein as a Sensitive Liquid Biopsy Marker for Early Detection of Breast Cancer. (30th August 2021) - Bartkowiak, Kai; Heidrich, Isabel; Kwiatkowski, Marcel; Banys-Paluchowski, Maggie; Andreas, Antje; Wurlitzer, Marcus; Geffken, Maria; Voß, Hannah; Zeller, Tanja; Blankenberg, Stefan; Peine, Sven; Joosse, Simon A; et al.
Abstract: Background: Despite recent progress in liquid biopsy technologies, early blood-based detection of breast cancer is still a challenge. Methods: We analyzed secretion of the protein cellular communication network factor 1 (CCN1, formerly cysteine-rich angiogenic inducer 61) in breast cancer cell lines by an enzyme-linked immunosorbent assay (ELISA). Soluble CCN1 in the plasma (2.5 µL) of 544 patients with breast cancer and 427 healthy controls was analyzed by ELISA. The breast cancer samples were acquired at the time of primary diagnosis prior to neoadjuvant therapy or surgery. A classifier was established on a training cohort of patients with breast cancer and age-adapted healthy controls and further validated on an independent cohort comprising breast cancer patients and healthy controls. Samples from patients with benign breast diseases were investigated as additional controls. Samples from patients with acute heart diseases (n = 127) were investigated as noncancer controls. The diagnostic accuracy was determined by receiver operating characteristic using the parameters area under the curve, sensitivity, and specificity. Results: CCN1 was frequently secreted by breast cancer cell lines into the extracellular space. Subsequent analysis of clinical blood samples from patients with breast cancer and age-adjusted healthy controls revealed an overall specificity of 99.0% and sensitivity of 80.0% for cancer detection. Remarkably, 81.5% of small T1 cancers were already CCN1-positive, while CCN1 concentrations in patients with benign breast lesions were below the threshold for breast cancer detection. Conclusions: Circulating CCN1 is a potentially novel blood biomarker for the detection of breast cancer at the earliest invasive stage.